Translation for Reading Aloud - Dollerup, Cay (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractThe article takes a look at the translation of children’s literature intended for reading aloud. The pragmatic (or theoretical) point of departure is a ‘narrative contract’ between the child (audience) and the reader as in the oral tradition of yesteryear. It is therefore argued that, at least initially, children’s literature for reading aloud was a continuation of the narrative tradition in the extended family adapted to the conditions and mores of the nuclear family. The nuclear family was a 19th century innovation promoted by the new middle classes, and they best carried on the narrative tradition by means of stories such as those of the brothers Grimm in Germany and Hans Christian Andersen in Denmark. Referring to an informal questionnaire among Translation Studies scholars covering eleven countries, it is concluded that the tradition of reading aloud for children is alive and well. This leads to a model for the translational situation for read-aloud literature that calls for guiding principles in the exploration of differences between ‘originals’ and ‘translations.’ Having introduced such layers, viz. the structural, the linguistic, the content and intentional ones, a paratextual and chronological layer are also called for, because of the ubiquity of modern co-prints and the need to introduce diachronic perspectives. The article discusses decision-makers in the process of translation, such as publishers and the like, and also briefly views questions of translational traditions before it discusses translations of the Grimm Tales into English and Danish, to conclude that there are two different schools of ‘respectable translators,’ one targeting stories for reading aloud and another for silent reading, even though the translators may not be aware of this. The final part takes up questions concerning the translation of names, rhymes, and a highly complex text which is discussed in depth. The conclusion is that translation for reading aloud is an art requiring great competence of translators. It also ought to attract more attention from Translation Studies scholars because it questions fundamentals in translation work that are also found in other types of translation.Readers should read aloud the passages cited in order to appreciate the commentary!